2002
DOI: 10.1080/08957950212431
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure-Temperature Processing as an Alternative for Preserving Basil

Abstract: In this study the effect of sterilisation by high pressure (HP) on the quality of basil was compared to conventional processing techniques. By means of freezing, or blanching followed by drying, microbial reduction of spores was maximal one-log. Pulsed HP-temperature treatment yielded a reduction of the natural occurring flora of more than 3 log CFU=g product. The essential oil content in basil consisted mainly of methylchavicol and linalool. HP sterilisation preserved these compounds in contrast to the equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 2 publications
1
18
0
1
Order By: Relevance
“…For example, sterilization of tomato puree was achieved by a 2 pulse treatment at 700 MPa and a 90°C starting temperature [36]. A comparison of a conventional heat and an equivalent sterilization pulsed PATP treatment showed that the latter yielded a higher linalool and methylchavicol retention and thus, allowing a higher retention of basil aroma [25]. However, an assessment of the advantages of pressure pulsing should consider the additional energy and equipment wear costs.…”
Section: Introductionmentioning
confidence: 98%
“…For example, sterilization of tomato puree was achieved by a 2 pulse treatment at 700 MPa and a 90°C starting temperature [36]. A comparison of a conventional heat and an equivalent sterilization pulsed PATP treatment showed that the latter yielded a higher linalool and methylchavicol retention and thus, allowing a higher retention of basil aroma [25]. However, an assessment of the advantages of pressure pulsing should consider the additional energy and equipment wear costs.…”
Section: Introductionmentioning
confidence: 98%
“…The effect of such elevated pressures on organoleptic properties of produce/herbs varies depending on the food (Chauvin et al, 2005;Arroyo, Sanz, & Préstamo, 1999;Krebbers, Matser, Koets, Bartels, & Van Den Berg, 2002;Garcia-Palazon, Suthanthangjai, Kajda, & Zabetakis, 2004;Suthanthangjai, Kajda, & Zabetakis, 2005;Tangwongchai, Ledward, & Ames, 2000). More research is needed to determine the various HPP treatment conditions capable of inactivating coccidian parasites on produce and whether such conditions also inactivate other deleterious enzymes and microorganisms associated with produce while maintaining desirable fresh-like characteristics.…”
Section: Discussionmentioning
confidence: 95%
“…Stwierdzono bowiem, że podczas przechowywania warzyw traktowanych ciśnieniem w temperaturze pokojowej zielona barwa roślin może zmieniać się w jasnożółtą w wyniku biochemicznych procesów takich, jak np. reakcje enzymatycznego utleniania [21,22].…”
Section: Wpływ Wysokiego Ciśnienia Na Barwę Owoców I Warzyw Oraz Ich unclassified